Progesterone use in assisted reproductive technology. (November 2020) - Labarta, Elena; Rodríguez, Cristina
Abstract: Progesterone is the main hormone in the luteal phase. It plays a key role in preparing the uterus for a possible pregnancy, and in maintaining it after it has occurred. In assisted reproduction treatments, there is usually a luteal phase deficiency, so it is necessary to supplement this critical phase to obtain the best results, not only of implantation but also of ongoing pregnancy. Among all the available options, exogenously administered progestogens are the most used, as they have proven their efficacy and safety. This review will address the most relevant aspects of luteal phase support with progesterone in the different scenarios an embryo transfer can be performed, such as the stimulated cycle, the artificial cycle, or the natural cycle. Although there is no evidence of the perfect protocol for all patients, recent studies point to the need of individualizing luteal phase support according to the needs of each patient. Highlights: Progesterone treatment is recommended in ART cycles to enhance embryo implantation and decrease the risk of miscarriage. In stimulated cycles, exogenous P is highly recommended and should be initiated the day after oocyte retrieval. In artificial cycles, exogenous P is absolutely needed as no endogenous production of P is present. In natural cycles, exogenous P might improve pregnancy outcomes. Serum P levels in the mid-luteal phase relate to the chances of pregnancy. Thus, monitoring P levels and individualizing LPS is recommended.